Consulting the Past Creating a National History Curriculum in Aotearoa New Zealand - Neill C; Belgrave M; Vilanova Miranda De Oliveira G (UTS ePRESS)
In many countries, the development of national history curricula has been politically controversial, causing great public interest and concern. Such controversies tend to bring into tension diverse political, social and cultural voices and their interests in a nation’s history, expressing the historical consciousness of a society. At the extreme, ‘history wars’ emerge over what is prioritised for learning, and how it is learnt, especially when historical interpretations clash with political agendas. In this article we explore these ideas through the responses of different sectors to the development of Aotearoa New Zealand's first national history curriculum. By looking at the responses of teachers, academic historians, politicians and the community at large, we attempt to explain why the debate so far has been professional rather than polemical, and why the country’s ‘history wars’ have only involved a few skirmishes at the edges of political debate.
(c) The Author/s
Keywords: 2102 Curatorial and Related Studies; 2103 Historical Studies